2016
DOI: 10.1021/jacs.5b13129
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding of Rimantadine Enantiomers to Influenza A M2 Proton Channel

Abstract: Rimantadine hydrochloride (α-methyl-1-adamantane-methalamine hydrochloride) is a chiral compound which exerts antiviral activity against the influenza A virus by inhibiting proton conductance of the M2 ion channel. In complex with M2, rimantadine has always been characterized as a racemic mixture. Here, we report the novel enantioselective synthesis of deuterium-labeled (R)- and (S)-rimantadine and the characterization of their protein-ligand interactions using solid-state NMR. Isotropic chemical shift changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 26 publications
(57 reference statements)
7
50
3
1
Order By: Relevance
“…The S31 and G34 resonance frequencies were similar for both 2-R and 2-S. These results provided an experimental evidence that both enantiomers bind strongly and the binding site and orientation of the drug in the pore are similar for the two enantiomers as mentioned in ref 23. However, the authors reported the appearance of an additional resonance of medium intensity for the 2-S enantiomer at 115/ 63 ppm close to the frequencies of the S31 resonance of the unbound M2 state at ∼114/62 ppm and suggested a weaker binding of 2-S.…”
Section: Acs Medicinal Chemistry Letterssupporting
confidence: 79%
See 3 more Smart Citations
“…The S31 and G34 resonance frequencies were similar for both 2-R and 2-S. These results provided an experimental evidence that both enantiomers bind strongly and the binding site and orientation of the drug in the pore are similar for the two enantiomers as mentioned in ref 23. However, the authors reported the appearance of an additional resonance of medium intensity for the 2-S enantiomer at 115/ 63 ppm close to the frequencies of the S31 resonance of the unbound M2 state at ∼114/62 ppm and suggested a weaker binding of 2-S.…”
Section: Acs Medicinal Chemistry Letterssupporting
confidence: 79%
“…The distance between the adamantyl ring and the center of mass between the four A30 (Ad-A30) for 1−3 was measured ∼1 Å, and the distance CH 3 (lig. )-G34Ca for 2-R, 2-S, and 3 was 2.9, 3.2 and 2 Å respectively, close to the REDOR measurements for 2-R, 2-S. 23 The adamantyl ring was embraced by the V27 and A30 side chains, which defined the binding site of the ligands. Compounds 1, 2-R, 2-S, and 3 form hydrogen bonds (average of three hydrogen bonds) through the ammonium group with neighboring water molecules which are positioned between the ligand and H37 residues.…”
Section: Acs Medicinal Chemistry Letterssupporting
confidence: 78%
See 2 more Smart Citations
“…10) and membrane protein architecture by Griffin and co-workers (Andreas et al, 2015). REDOR distance measurements are also used for the studies of ligand-protein interactions, including binding of amantadine and its derivatives in the M2 channel by Cross (Wright et al, 2016) and Hong (Cady et al, 2010) and retinal binding in bacteriorhodopsin (Helmle et al, 2000). REDOR-derived distances can also indicate changes in protein or nucleic acid conformation upon ligand binding, demonstrated for tat peptide-bound TAR RNA of HIV-1 (Olsen et al, 2005).…”
Section: Current Methodology For Structural and Dynamics Analysis mentioning
confidence: 99%